Storage and degradation kinetics of physicochemical and bioactive attributes in microalgal-derived fucoxanthin-rich microcapsules - Foo, Su Chern; Yusoff, Fatimah Md; Khong, Nicholas M.H. (Elsevier, 2024)
Microencapsulation can improve carotenoid stability by slowing down degradation. Studies on the production and processing effects of microencapsulated carotenoids were reported in the past however long-term storage studies on fucoxanthin stability remains limited. This study investigated the effects of an eighteen-week storage period across four conditions on fucoxanthin derived from the diatom, Chaetoceros calcitrans. The fucoxanthin powders were prepared using two microencapsulation methods i.e., freeze drying and spray drying. Briefly, the microcapsules produced were stored in amber bottles under room temperature (25 °C) or refrigerated (4 °C) in the dark or in the presence of light. Samples were collected every two weeks where the physicochemical characteristics, carotenoid stability and antioxidant activity were evaluated. It was found that the freeze-dried microcapsule stored in 4 °C showed significantly (p < 0.05) better carotenoid retainment (7.5 times more) and antioxidant outcomes (3.5 times higher), as compared to the spray-dried microcapsule stored in 25 °C light. All microcapsules were found to be mainly comprised of the carotenoids fucaxanthin, dehydro fucoxanthin acetate, capsanthone, antheraxanthin, and celaxanthin. The major carotenoid identified was fucoxanthin where correlation studies showed it was responsible for the antioxidant activities and stability of the produced microcapsules. Overall, both freeze-dried and spray-dried fucoxanthin microcapsules followed a first-order kinetic degradation reaction and the recommended storage condition for fucoxanthin microcapsules was ranked as follows 4 °C (dark) > 25 °C (dark) > 40 °C (dark) > 25 °C (light). This finding offer useful insights into optimizing fucoxanthin microencapsulation methods, maintaining product quality during storage and distribution, and ensuring compliance with quality standards of fucoxanthin-based products available to consumers across the production and distribution chain. © 2023 The Author(s)